A micro-architecturally biomimetic collagen template for mesenchymal condensation based cartilage regeneration. (15th January 2016) - Younesi, Mousa; Goldberg, Victor M.; Akkus, Ozan
Graphical abstract: Abstract: The unique arcade-like orientation of collagen fibers enables cartilage to bear mechanical loads. In this study continuous-length aligned collagen threads were woven to emulate the interdigitated arcade structure of the cartilage. The weaving pattern provided a macropore network within which micromass cell pellets were seeded to take advantage of mesenchymal condensation driven chondrogenesis. Compression tests showed that the baseline scaffold had a modulus of 0.83 ± 0.39 MPa at a porosity of 80%. The modulus of pellet seeded scaffolds increased by 60% to 1.33 ± 0.37 MPa after 28 days of culture, converging to the modulus of the native cartilage. The scaffolds displayed duress under displacement controlled low-cycle fatigue at 15% strain amplitude such that load reduction stabilized at 8% after 4500 cycles of loading. The woven structure demonstrated a substantial elastic recoil where 40% mechanical strain was close to completely recovered following unloading. A robust chondrogenesis was observed as evidenced by positive staining for GAGs and type II collagen and aggrecan. Dimethyl methylene blue and sircol assays showed GAGs and collagen productions to increase from 3.36 ± 1.24 and 31.46 ± 3.22 at day 3 to 56.61 ± 12.12 and 136.70 ± 12.29 μg/μg of DNA at day 28 of culture. This woven collagen scaffold holds a significant potential for cartilage regeneration with shorter in vitro culture periods due to functionally sufficient mechanical robustness at the baseline. In conclusion, the mimicry of cartilage's arcade architecture resulted in substantial improvement of mechanical function while enabling one of the first pellet delivery platforms enabled by a macroporous network. Statement of significance: Mesenchymal condensation is critical for driving chondrogenesis, making high density cell seeding a standard in cartilage tissue engineering. Efforts to date have utilized scaffold free delivery of MSCs in pellet form. This study developed a macroporous scaffold that is fabricated by weaving highly aligned collagen threads. The scaffold can deliver high density cell condensates while providing mechanical stiffness comparable to that of cartilage. The scaffold also mimicked the arcade-like orientation of collagen fibers in cartilage. A highly robust chondrogenesis was observed in this mesenchymal cell pellet delivery system. Baseline mechanical robustness of this scaffold system will enable delivery of cell pellets as early as three days.